A Comparison of Treatment-Seeking Behavioral Addiction Patients with and without Parkinson’s Disease - Sauvaget, Anne; Jiménez-Murcia, Susana; Fernández-Aranda, Fernando; Granero, Roser; Grall-Bronnec, Marie; Victorri-Vigneau, Caroline; Bulteau, Samuel; Derkinderen, Pascal; Vanelle, Jean M.; Hakansson, Anders; Mestre-Bach, Gemma; Steward, Trevor; et al. (Frontiers in Psychiatry, 2017)
The administration of dopaminergic medication to treat the symptoms of Parkinson’s disease (PD) is associated with addictive behaviors and impulse control disorders. Little is known however on how PD patients differ from other patients seeking treatments for behavioral addictions. The aim of this study was to compare the characteristics of behavioral addiction patients with and without PD. N=2,460 treatment-seeking men diagnosed with a behavioral addiction were recruited from a university hospital. Sociodemographic, impulsivity (Barratt Impulsiveness Scale; BIS-11), and personality (Temperament and Character Inventory-Revised; TCI-R) measures were taken upon admission to outpatient treatment. Patients in the PD group were older and had a higher prevalence of mood disorders than patients without PD. In terms of personality characteristics and impulsivity traits, PD patients appeared to present a more functional profile than PD-free patients with a behavioral addiction. Our results suggest that PD patients with a behavioral addiction could be more difficult to detect than their PD-free counterparts in behavioral addiction clinical setting due to their reduced levels of impulsivity and more standard personality traits. As a whole, this suggests that PD patients with a behavioral addiction may have different needs from PD-free behavioral addiction patients and that they could potentially benefit from targeted interventions.